Implementation of Wemos D1 Microcontroller to Monitor Water pH in Real Time at WWTP (Waste Water Treatment Plant) Based on Internet of Things - Arif Siswandi; Fajar Sigit Srijati; A. Yudi Permana (Jurnal Mantik, 2021)
Industrial wastewater treatment must pay attention to the following points, including the volume of wastewater to be treated, the expected quality of the water resulting from the WTP process, the ease of wastewater management, energy sources, and low process operational costs. This study aims to reduce the process from wastewater sampling to laboratory analysis to obtain the results of monitoring the pH of the water. In this study, the authors make a WWTP automation system for monitoring pH that can be carried out in real time along with the development of industry 4.0. By using Wemos D1 which is integrated by the internet of things through the internet network from a Wi-Fi router. Data from pH monitoring results can be seen in real time through a user interface that is accessed via a smartphone or PC with a server and client distance of more than 50 meters. By using a real-time pH monitoring system, you can cut down the pH monitoring process and view monitoring results through the user interface.